The Effectiveness of Case Study Learning Methods Improving Online Learning Activity in The Children and Adolescent Development Psychology UIN Surakarta - Muhammad Bagus Azmi; Aprillia Setyaning Normalisa Putri; Sabarudin Sabarudin; Kholilurrohman Kholilurrohman (Abjadia, 2022)
Since the covid outbreak, online learning has been widely implemented and comprehensively applied. Problems with student participation in the teaching and learning process are quite common. The goal of this research was to see how efficient the case study learning method was in increasing online lecture activity in Child and Adolescent Development Psychology class 3A at BKI UIN Surakarta. Observation, interviews, and questionnaires were employed as part of the qualitative method. The implementation or application of case study learning methods in online lectures begins with providing short but solid material. Problems related to the material are given to be solved together. Educators will become facilitators by allowing students to express opinions, feedback, or questions. This study also discovered that student activity rose, notably in terms of learning enthusiasm, confidence, and optimism.